2000
DOI: 10.1002/(sici)1097-4636(20000605)50:3<405::aid-jbm15>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Alginate hydrogel linked with synthetic oligopeptide derived from BMP-2 allows ectopic osteoinductionin vivo

Abstract: Bone morphogenetic proteins (BMP) are unique molecules with a specific biological activity for inducing ectopic bone formation when implanted with a suitable carrier matrix. However, incorporation of BMP into the carrier has disadvantages, including early burst release and protein degradation in biological environments. Therefore, we considered that the next greatest challenge in achieving successful clinical use was the development of a carrier system for site-specific delivery of the morphogenetic signal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
128
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(129 citation statements)
references
References 27 publications
0
128
0
1
Order By: Relevance
“…Delivery of growth factors for morphogenesis and differentiation of stem cells have been successfully verified in various biomaterials [92]. Growth factors have been covalently modified on the surface of biomaterials to provide progrowth and pro-survival factors which may enhance long-term in vivo survival and differentiation of stem cells [93,94]. Growth factors released from biomaterials via diffusion, cell-mediated proteolysis, or in response to mechanical stimuli have been successfully incorporated for in vitro and in vivo regenerative applications [92,95].…”
Section: Growth Factors-mentioning
confidence: 99%
“…Delivery of growth factors for morphogenesis and differentiation of stem cells have been successfully verified in various biomaterials [92]. Growth factors have been covalently modified on the surface of biomaterials to provide progrowth and pro-survival factors which may enhance long-term in vivo survival and differentiation of stem cells [93,94]. Growth factors released from biomaterials via diffusion, cell-mediated proteolysis, or in response to mechanical stimuli have been successfully incorporated for in vitro and in vivo regenerative applications [92,95].…”
Section: Growth Factors-mentioning
confidence: 99%
“…Previous reports showed that a synthetic peptide corresponding to residues 68-87 (NSVNSKIPKACCVPTELSAI) of the knuckle epitope of human BMP-2 could induce ectopic bone formation in vivo [21,22], suggesting that this sequence is the functional domain of the mature human BMP-2. Another study identified that a peptide corresponding to amino acids 73-92 (KIPKASSVPTELSAISTLYL) of human BMP-2, which substituted Cys78, Cys79, and Met89 with Ser (S), Ser (S), and Thr (T), respectively, induced a higher alkaline phosphatase (ALP) activity than the original 68-87 peptide [22].…”
Section: Effect Of the Pfbmp-2 Mature Domain On The Differentiation Omentioning
confidence: 99%
“…De Mel et al have recently published a review on biofunctionalization of biomaterials for accelerated in situ endothelialization (de Mel et al, 2008). Not only complete GFs can be attached to scaffold surfaces, but also oligopeptides such as those derived from BMP-2 or BMP-7 that have been immobilized on alginate hydrogels and glass, respectively (Kirkwood et al, 2003;Saito et al, 2003;Suzuki et al, 2000). These in vitro studies, performed with a murine multipotent MSC culture or with primary rat calvarial osteoblastic cell populations showed that immobilized oligopeptides may have the capacity to induce osteoblastic differentiation and mineralization in a more predictable manner than the entire GF.…”
Section: Growth Factorsmentioning
confidence: 99%
“…This might be attributed to the lower complexity of the molecule and therefore increased stability. Implantation of a BMP-2 derived oligopeptide covalently coupled to alginate into the calf muscle of rats resulted in ectopic bone formation (Suzuki et al, 2000). Synthetic peptide mimics have also been applied for the promotion of angiogenic responses (X.…”
Section: Growth Factorsmentioning
confidence: 99%